Progressive taxation, macroeconomic stabilization and efficiency in Europe - Martinez-Mongay, Carlos; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2005)
The paper contributes to the debate on the stability/efficiency tradeoff of automatic stabilizers. A simple AD-AS two-country model is presented and illustrates circumstances where a reduction in taxes can foster stabilization. The testable implication from the model is that tax cuts can either increase or decrease volatility depending on the structure of the taxation system. Hence, lowering taxes for efficiency purposes may have not cost in terms of stabilization. This implication is tested for OECD countries over the period 1960-2000 taking account of the endogeneity and omitted variables issues identified in the literature. We found acceptably robust evidence that the size of governments in OECD countries has played a stabilizing role for both output and inflation. However, the relationship between government size and macroeconomic stability is not linear. The composition of public finances, in particular the tax mix, matters for output and price volatility. Distorting taxes, namely taxes on labor, might have negative effects on macroeconomic stability. Consequently, the potential trade off between stability and flexibility might not exist.
Economic Papers